Bahasa indonesa - Parwati, Laeli (IAINU Kebumen, 2022)
This study aims to analyze the role of the principal in improving the quality of education at the Lukulo Natural School, Kebumen. The research was carried out at the Lukulo Nature School, Kebumen. The participant of this research is the principal of the Lukulo Natural School, Kebumen. The author uses descriptive qualitative research methods. Data were collected through observation, interviews, and documentation. The research resulted in the finding that the principal of the Alam Lukulo Kebumen School applied several leadership styles to improve the quality of education at the Lukulo Kebumen Natural School in the form of telling style (giving work to subordinates and directing), selling style (making clear rules), participating style (solving problems together). , and style delegation (giving full responsibility to the teacher). Keywords: Role, Principal, Quality of Education, School of Nature